PERAN LEMBAGA PENDIDIKAN WAKAF DALAM MEMBENTUK KARAKTER BERTOLERANSI (ZISWAF: Jurnal Zakat dan Wakaf, 2017)
The importance of the Quranic principle in the Qur>an is actually nothing but a departure from social reality, that diversity and diversity are social facts. Nevertheless, for some people it still assumes that diversity is a threat, but for some others diversity undermines the monism that is inherent in tribal, national and religious clothes. The number of social conflicts that occur in society today is pointed out as an indication that some parties are still unwilling and not ready to accept the diversity even many ways that are used in rejecting the fitrah and destiny of God, which is by forming a religious understanding that rejects various forms of understanding that lead to diversity include the diversity of ideology and contemporary-modern thought theory. Seeing this fact, it is important to immerse tolerance within the framework of diversity in the life of society, nation and state. Tolerance is needed and become a pillar in realizing a life of mutual respect for each other so as to create a harmonious life. To realize it all required the role of educational institutions is no exception wakaf educational institutions where it is considered to have a noble and great role in the history of human life that is shaping the character of learners who are capable, independent, creative, democratic, responsible and tolerant tailored to the concept of curriculum based on values  of tolerance according to Islamic teachings.